Hard inorganic foam
By using components such as polymers and surfactants obtained by combining polyisocyanate and polyol or polyamines, the compressive strength and mechanical properties of inorganic foam are improved, and the problem of insufficient mechanical stability of inorganic foam materials is solved. It is suitable for building isolation Thermal and sound insulation applications.
Patent Information
- Application Number
- CN202380041624.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing inorganic foam materials have low mechanical stability, especially when installed in building thermal insulation systems, and the compressive strength is not sufficient to meet construction needs.
Using polymers obtained from a combination of polyisocyanate and polyol or polyamines as mineral binders, combining surfactants and particles to form a rigid inorganic foam material with anionic groups, and increasing compressive strength through polymer blends and formulated with superplasticizer to reduce the risk of cement hydration collapse.
It significantly improves the compressive strength and mechanical properties of inorganic foam, forms a low-density, closed-cell structure, has good thermal insulation, sound insulation and fire resistance, and is suitable for building thermal insulation, sound insulation and passive fire protection systems.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a rigid inorganic foam material. The rigid inorganic foam material of the invention comprises at least one cured mineral binder, at least one surfactant and / or particles and at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines, the polymer comprising anionic groups. The invention also relates to a method for preparing the rigid inorganic foam and its use as a product or in a system for thermal insulation, sound insulation, lightweight construction and / or passive fire protection. Background of the Invention
[0002] Inorganic foams have many uses in the construction industry. For example, they are used as materials in thermal insulation systems. A particular advantage of inorganic foams is their low flammability, especially compared to organic materials such as XPS or PIR commonly used in thermal insulation systems. Another advantage is that inorganic foams are lightweight and can therefore be easily incorporated into buildings, for example as facades or roofs.
[0003] However, the mechanical stability of inorganic foam materials, especially cementitious foam materials, is usually very low. The low mechanical stability makes the installation of insulation systems containing inorganic foams difficult.
[0004] WO 2019 / 038105 discloses inorganic hybrid foams comprising a mineral binder, at least one polymer derived from an ethylenically unsaturated monomer or from a combination of a polyisocyanate with a polyol and / or a polyamine, at least one surfactant, at least one thickener and water. These foams are reported to have increased compressive strength and better adhesion to concrete. However, polymers obtained in particular from a combination of polyisocyanates and polyols and / or polyamines are only disclosed in WO 2019 / 038105 in very general terms.
[0005] In particular, it is desirable to further increase the compressive strength of the inorganic foam disclosed in WO 2019 / 038105, which would facilitate the use of such inorganic foam in thermal insulation systems for buildings and for other purposes in the construction industry. Summary of the invention
[0006] The object of the present invention is to provide an inorganic foam with increased mechanical strength. In particular, the inorganic foam of the present invention should have a high compressive strength. The inorganic foam of the present invention can preferably be used as thermal and / or acoustic insulation, lightweight construction and / or passive fire protection. Another object of the present invention is to provide a thermal insulation system and / or acoustic insulation system and / or passive fire protection system, in particular a system which can be applied to buildings, preferably facades, floors and / or roofs.
[0007] These objects are achieved by the subject matter claimed in the independent claims.
[0008] It has surprisingly been found that the compressive strength of inorganic foams can be increased by including certain specific polymers obtained from a combination of polyisocyanates and polyols and / or polyamines, said polymers comprising anionic groups. It has further been found that the additional use of certain polymer blends consisting of polyvinyl alcohol and further polymers based on vinyl esters, (meth)acrylates, vinyl aromatics, vinyl halides and / or olefins can further increase the compressive strength of inorganic foams.
[0009] Another advantage of the rigid inorganic foams of the present invention is that they can be formulated with small amounts of superplasticizers for cement. This is particularly advantageous since such superplasticizers are known to delay cement hydration which, in the case of cement-based inorganic foams, can cause the foam to collapse before curing has occurred. The polymers obtained from the combination of polyisocyanates and polyols and / or polyamines, which polymers contain anionic groups, can be used as plasticizers for inorganic binders, particularly cement, thus reducing the need for additional superplasticizers.
[0010] The polymers obtained from the combination of polyisocyanates and polyols and / or polyamines, which polymers contain anionic groups, lead to the formation of rigid inorganic foams with a closed-cell structure. This is beneficial because the closed-cell structure generally also leads to a higher compressive strength of the foam compared to an open-cell structure at the same density. In addition, the thermal insulation properties are generally improved in closed-cell foam structures.
[0011] The rigid inorganic foam of the present invention has one or more of the following advantages:
[0012] Low density,
[0013] Closed-cell foam structure,
[0014] increased mechanical strength, in particular compressive strength, impact resistance and / or flexural strength,
[0015] Low water absorption,
[0016] Quick drying characteristics after wetting,
[0017] Non-flammable,
[0018] Low thermal conductivity,
[0019] High sound damping properties.
[0020] Further aspects of the invention are the subject matter of the independent claims. Preferred embodiments of the invention are the subject matter of the dependent claims. DETAILED DESCRIPTION
[0021] In a first aspect, the present invention relates to a rigid inorganic foam comprising: a) at least one cured mineral binder, b) at least one surfactant S and / or particles N, and c) at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine, characterised in that at least one of the at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine comprises anionic groups.
[0022] In this article, the term "rigid inorganic foam" refers to a material consisting of bubbles embedded in a hard inorganic matrix. The bubbles can be in the form of holes and / or pores. The content of bubbles embedded in the inorganic matrix can vary in the range of 20-99% by volume, preferably 20-98% by volume, and especially 50-95% by volume relative to the total volume of the hard inorganic foam. In other words, the term "rigid inorganic foam" refers to an inorganic material with a high porosity. The hard inorganic foam may contain bubbles in the form of an interconnected network (open-cell foam) or in an isolated form (closed-cell foam) or as a mixture of interconnected and isolated pores. Closed-cell foam is preferred in this article. The gas can be any gas, preferably air. The hard inorganic matrix is substantially dry. The hard inorganic foam of the present invention is substantially free of water. Substantially free of water means that the amount of water is less than 5% by weight, preferably less than 1% by weight, and especially less than 0.5% by weight, in each case relative to the total weight of the hard inorganic foam. Water adsorbed on the surface of the otherwise substantially dry hard inorganic foam is not included in this definition. The hard inorganic matrix comprises at least one solidified mineral binder. The inorganic matrix may comprise other organic and / or inorganic materials. Preferably, at least 51% by weight of the inorganic matrix, preferably at least 70% by weight, more preferably at least 80% by weight, relative to the total dry weight of the inorganic matrix in each case is composed of inorganic materials. Of course, the inorganic matrix also comprises at least one surfactant S and / or particle N and a polymer obtained by a combination of polyisocyanates and polyols and / or polyamines. Therefore, the total content of inorganic materials in the inorganic matrix is less than 100% by weight relative to the total dry weight of the inorganic matrix. The term "hard" or "hard" can be associated with a certain compressive strength of the inorganic foam. Preferably, the hard inorganic foam of the present invention has a compressive strength of at least 10kPa, more preferably at least 50kPa, and even more preferably at least 100kPa. The compressive strength can be measured under 10% extrusion according to standard DIN EN 826. The porosity of a rigid inorganic foam or porous inorganic material can be measured by mercury porosimetry according to standard ISO 15901-1:2016. However, it is usually more convenient to consider the dry density of the porous material. In this article, a high porosity is associated with a low density. In other words, the lower the density, the higher the porosity of the rigid inorganic foam. Throughout this article, when density is mentioned or density values are given, these densities are measured gravimetrically. The preferred measurement method is as follows: a sample cube with a size of 10×10×10 cm is first cut from the material and then dried in an oven at 70°C until the weight of the material remains constant. The weight of the sample cube is then measured, and the density of the material (in g / l) is obtained by dividing the measured weight of the cube (in g) by 1 L.
[0023] In the context of the present invention, the term "low density" stands for a density of not more than 500 g / l.
[0024] According to an embodiment, the density of the rigid inorganic foam according to the invention does not exceed 500 g / l, in particular does not exceed 300 g / l, in particular does not exceed 200 g / l. For example, the density is 20-500 g / l, preferably 50-300 g / l, more preferably 70-200 g / l. However, higher densities are also possible in principle.
[0025] Thus, preferred rigid inorganic foams according to the invention are substantially free of water, have a compressive strength of at least 10 kPa, more preferably at least 50 kPa, even more preferably at least 100 kPa, measured at 10% compression according to standard DIN EN 826, and a density of 20 to 500 g / l, preferably 50 to 300 g / l, more preferably 70 to 200 g / l. Particularly preferred rigid inorganic foams according to the invention additionally have a closed-cell structure.
[0026] Optionally, a further liquid phase may be present in the rigid inorganic foams according to the invention.
[0027] In the present context, the term "cured mineral binder" denotes a substance that is inorganic in nature and at least partially cured, preferably fully cured. Curing may occur by chemical reaction of the mineral binder, in particular by hydration, or by physical reaction of the mineral binder, in particular by drying. Preferably, the reaction product is not water-soluble.
[0028] According to a preferred embodiment, the mineral binder is selected from cement, gypsum, lime, magnesium oxide, aluminum oxide, geopolymers, latent hydraulic binders and / or pozzolans.
[0029] The cement may in particular be a Portland cement of the CEM I, CEM II, CEM III, CEM IV or CEMV type as described in standard EN 197-1, a calcium aluminate cement as described in standard EN 14647, and / or a calcium sulphoaluminate cement. The term "gypsum" is intended to include the various forms of CaSO4, in particular CaSO4 anhydrite, CaSO4 α- and β-hemihydrates and CaSO4 dihydrate. The term "lime" is intended to include natural hydraulic lime, formulated lime, hydraulic lime and atmospheric lime as described in standard EN 459-1:2015. The term "alumina" means aluminium oxide, aluminium hydroxide and / or aluminium oxy-hydroxides such as gibbsite and boehmite, calcined or flash-calcined aluminium oxide, aluminium oxide obtained by the Bayer process, hydratable aluminium oxides such as amorphous mesophase aluminium oxide and rho-phase aluminium oxide. Pozzolans and latent hydraulic materials represent in particular type II concrete additives having latent hydraulic and / or pozzolanic properties according to EN 206-1. Pozzolans and latent hydraulic materials are preferably selected from slag, clay, calcined clay, in particular metakaolin, kiln dust, microsilica, fly ash, pyrogenic silica, precipitated silica, silica fume, zeolites, rice husk ash, burned oil shale and natural pozzolans, such as pumice, trachyte and finely ground limestone.
[0030] Therefore, the solidified mineral binder is preferably a fully hydrated or fully dried cement, gypsum, lime, magnesium oxide, aluminum oxide, geopolymer, latent hydraulic binder and / or pozzolan in this context. Particularly preferably, the solidified mineral binder is a fully hydrated Portland cement or a fully hydrated aluminate cement, or a fully dried gypsum, or a mixture thereof.
[0031] According to an embodiment, the proportion of cured mineral binder is 9-99% by weight, preferably 25-85% by weight, more preferably 40-80% by weight, relative to the total dry weight of the rigid inorganic foam.
[0032] At least one surfactant S can be selected from nonionic, anionic, cationic, zwitterionic and amphiphilic compounds and proteins or mixtures thereof. According to some embodiments, a combination of nonionic and anionic surfactants is used. Suitable anionic surfactants are dibenzofuran sulfonates, alkanes and alkylbenzene sulfonates, alkylnaphthalene sulfonates, olefin sulfonates, alkyl ether sulfonates, alkyl sulfates, alkyl ether sulfates, α-sulfo fatty acid esters, acylaminoalkane sulfonates, acyl isosulfurates, alkyl ether carboxylates, N-acyl sarcosinates, alkyl and alkyl ether phosphates. The example of suitable anionic surfactants includes C8-C18-alkyl sulfates, C8-C18-alkyl ether sulfates, C8-C18-alkyl sulfonates, C8-C18-alkylbenzene sulfonates, C8-C18-α-olefin sulfonates, C8-C18-sulfosuccinates, α-sulfo- C8-C18-fatty acid salts and C8-C18-fatty acid salts. Anionic surfactants are usually present as alkali metal salts, in particular as sodium salts. Examples of sodium salts of anionic surfactants are sodium lauryl sulfate, sodium myristyl sulfate, sodium cetyl sulfate, sodium sulfate of ethoxylated lauryl or myristyl alcohol with a degree of ethoxylation of 2 to 10, sodium lauryl or cetyl sulfonate, sodium hexadecylbenzenesulfonate, sodium C14 / C16-α-olefinsulfonate, sodium lauryl or cetylsulfosuccinate, disodium 2-sulfolaurate, sodium stearate or mixtures thereof. Suitable nonionic surfactants include alkylphenol polyglycol ethers, fatty alcohol polyglycol ethers, fatty acid polyglycol ethers, fatty acid alkanolamides, block copolymers, amine oxides, glycerol fatty acid esters, sorbitan esters or alkyl polyglucosides. Examples of suitable nonionic surfactants include C8-C18 fatty alcohol ethoxylates, block copolymers of ethylene oxide and propylene oxide, or C8-C18 alkyl polyglycosides or mixtures thereof. Examples of block copolymers are poloxamers. Poloxamers are block copolymers of ethylene oxide and propylene oxide, and preferred poloxamers contain 2-130 ethylene oxide units and 10-70 propylene oxide units. Examples of cationic surfactants are alkyl triammonium salts, alkyl benzyl dimethyl ammonium salts or alkyl pyridinium salts. Suitable zwitterionic surfactants are betaines. An example of zwitterionic surfactants is cocoamidopropyl betaine, particularly lauroamidopropyl betaine.
[0033] Both vegetable and animal proteins or mixtures thereof can be used as protein-based surfactants. Examples of proteins suitable for use as surfactants include keratin, hydrolyzed keratin, collagen, hydrolyzed collagen or soy-based proteins.
[0034] According to a preferred embodiment, the at least one surfactant S is chosen from nonionic and anionic surfactants, preferably from C14-C16 alkyl sulfonates, esters of 2-sulfo-succinic acid, alkyl polyglucosides or mixtures thereof, or cocoamidopropyl betaine, or protein-based surfactants.
[0035] According to one or more embodiments, the proportion of at least one surfactant S is 0.1-25% by weight, preferably 0.5-20% by weight, more preferably 1-15% by weight, relative to the total dry weight of the rigid inorganic foam.
[0036] The particles N of the present invention preferably have a particle size of 10 nm to 500 μm, preferably 20 nm to 300 μm, more preferably 25 nm to 150 μm, still more preferably 30 nm to 100 μm, especially 30 nm to 1 μm. The particle size can be determined by laser diffraction as described in ISO 13320:2009. In particular, a Mastersizer 2000 instrument with a Hydro 2000G dispersion unit and Mastersizer 2000 software from Malvern Instruments GmbH (Germany) is used. For example, isopropanol is suitable as a measuring medium. Preferably, the particle size of non-spherical or irregular particles is represented by the equispherical diameter of a sphere of equal volume. In the present invention, whenever a particle size range is given, the lower limit of the range represents the D10 value, while the upper limit of the particle size range given herein represents the D90 value of the corresponding particle size distribution.
[0037] According to some embodiments, the particles N of the present invention are nanoparticles. This means that the particles N have a particle size in the nanometer range, in particular a particle size D50.
[0038] In particular, the particles N are selected from inorganic particles, in particular from pure and mixed metal oxides, hydroxides, carbides, nitrides, phosphates, carbonates, silicates, sulfates. According to an embodiment, the particles N are selected from the following particles: clay, talc, silicon dioxide, calcium carbonate, ferrite, gibbsite, titanium oxide, zinc oxide, aluminum oxide, magnesium oxide, zirconium oxide, tin oxide, cerium oxide, spinel, aluminum hydroxide, calcium hydroxide, magnesium hydroxide, silicon carbide, boron carbide, silicon nitride, boron nitride, calcium phosphate, nickel carbonate, calcium carbonate, magnesium carbonate, silica fume, fly ash, quartz, ground glass, slag, calcium silicate, mullite, cordierite, zeolite, diatomaceous earth, cement, calcium sulfate and / or carbon black particles. In particular, the particles are silica particles.
[0039] According to another preferred embodiment, the particles are chosen from organic particles, especially polymer particles, in particular polystyrene particles and / or poly(methyl methacrylate) particles.
[0040] The proportion of particles N, if present, is in particular 1 to 50% by volume, in particular 2 to 20% by volume, especially 3 to 10% by volume, relative to the total volume of the hardened inorganic foam.
[0041] Rigid foam comprises at least one polymer obtained by the combination of polyisocyanate and polyol and / or polyamine.Such polymer comprises carbamate group and / or urea group.Other groups may also be included, such as allophanate group or biuret group.Polyurethane and / or polyurea are the common names of such polymer.For ease of reading, in the whole present invention, the term "polyurethane" will be used and means the polymer obtained by the combination of polyisocyanate and polyol and / or polyamine.Therefore, the term "polyurethane" includes polyurethane, polyurea and the polymer comprising other groups such as allophanate group or biuret group except carbamate group and / or urea group in this article.
[0042] According to an embodiment, the polyurethane of the invention comprises anionic groups in an amount such that the anionic charge density is 0.01-100 meq / g polymer, preferably 0.01-10 meq / g polymer, more preferably 0.05-1 meq / g polymer, still more preferably 0.2-0.5 meq / g polymer. Throughout the present invention, the term "meq" stands for "milliequivalent" and refers to the amount of anionic charge (in mmol).
[0043] The term "polyisocyanate" is intended to encompass organic molecules having more than one isocyanate group, including diisocyanates.
[0044] Suitable diisocyanates for preparing polyurethanes are aromatic, aliphatic or cycloaliphatic diisocyanates having a molecular weight of less than 500 g / mol. Examples of suitable aromatic diisocyanates are all isomers of toluene diisocyanate (TDI), in isomerically pure form or as a mixture of several isomers, naphthalene-1,5-diisocyanate (NDI), naphthalene-1,4-diisocyanate (NDI), diphenylmethane-4,4'-diisocyanate (MDI), diphenylmethane-2,4'-diisocyanate and mixtures of 4,4'-diphenylmethane diisocyanate with the 2,4'-isomer, xylylene diisocyanate (XDI), 4,4'-diphenyldimethylmethane diisocyanate, dialkyl and tetraalkyl diphenylmethane diisocyanates, 4,4'-dibenzyl diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate. Examples of suitable cycloaliphatic diisocyanates are hydrogenation products of the above-mentioned aromatic diisocyanates, such as 4,4'-dicyclohexylmethane diisocyanate (H12MDI), cyclohexane-1,4-diisocyanate, hydrogenated xylylene diisocyanate (H6XDI), 1-methyl-2,4-diisocyanato-cyclohexane, hydrogenated p-tetramethylxylylene diisocyanate (m-TMXDI, p-TMXDI). Other suitable diisocyanates are 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethyl-cyclohexane (isophorone diisocyanate, IPDI) and dimerized fatty acid diisocyanate. Examples of aliphatic diisocyanates include tetramethoxybutane-1,4-diisocyanate, butane-1,4-diisocyanate, hexane-1,6-diisocyanate (HDI), 1,6-diisocyanato-2,2,4-trimethylhexane, 1,6-diisocyanato-2,4,4-trimethylhexane, lysine diisocyanate and 1,12-dodecyl diisocyanate (C12DI). According to an embodiment, the diisocyanate is an aliphatic diisocyanate, preferably selected from IPDI, HDI and H12MDI, especially IPDI. According to a further embodiment, the diisocyanate is an aromatic diisocyanate, preferably selected from TDI and MDI.
[0045] Mixtures of different polyisocyanates can also be used to prepare the polyurethanes. Examples include toluene diisocyanate (TDI), naphthalene-1,4-diisocyanate (NDI), diphenylmethane 2,4′-diisocyanate (MDI), isophorone diisocyanate (IPDI) or isomers of hydrogenated 2,4′-MDI. According to an embodiment, polyisocyanates with isocyanate groups of different reactivity are used to prepare the polyurethanes.
[0046] The polyols suitable for preparing polyurethanes are polyols selected from polyether polyols or polyester polyols. Preferably, the polyols are organic molecules with two or three hydroxyl groups per molecule having a molecular weight of 200-3000 g / mol, preferably 400-2000 g / mol. Examples are difunctional and / or trifunctional polypropylene glycol or polyethylene glycol. A particularly useful example is linear difunctional polyethylene glycol monomethyl ether. Random and / or block copolymers of ethylene oxide and propylene oxide can also be used. Another group of polyether polyols that can be used to prepare polyurethanes is polytetramethylene glycol (poly(oxytetramethylene) glycol, polyTHF), which is prepared, for example, by acid polymerization of tetrahydrofuran.
[0047] Suitable polyols are also polyesters produced by condensation of dicarboxylic acids or tricarboxylic acids such as adipic acid, sebacic acid, glutaric acid, azelaic acid, undecanedioic acid, dodecanedioic acid, 3,3-dimethylglutaric acid, terephthalic acid, isophthalic acid, hexahydrophthalic acid, dimerized fatty acids or mixtures thereof with low molecular weight diols or triols such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, dimerized fatty alcohols, glycerol, trimethylolpropane or mixtures thereof. Another group of polyols used according to the invention are polyesters based on ε-caprolactone, also called polycaprolactones.
[0048] Polyester polyols of oleochemical origin can also be used. Such polyester polyols can be prepared, for example, by complete ring opening of epoxidized triglycerides of a fat mixture containing at least some olefinically unsaturated fatty acids with one or more alcohols having 1 to 12 carbon atoms and subsequent partial transesterification of the triglyceride derivatives into alkyl ester polyols having 1 to 12 carbon atoms in the alkyl group. This can be, for example, castor oil.
[0049] Further suitable polyols are polycarbonate polyols, polycaprolactone diols, dimer diols or hydroxy-functional polybutadienes.
[0050] Other suitable polyols are aliphatic alkylene glycols. These can be straight-chain or branched C2-C24 diols with OH groups at the ends of the carbon chains or on the side chains. Examples are ethylene glycol, propylene glycol, butanediol-1,4, pentanediol-1,5, hexanediol-1,6, heptanediol-1,7, octanediol-1,8 and their higher homologues or isomers. Also suitable are higher functionality alcohols such as glycerol, trimethylolpropane, pentaerythritol or sugar alcohols. However, such higher functionality polyols are less preferred and should only be present in small proportions in the polyol.
[0051] Further suitable polyols are dimethylolpropionic acid (DMPA), tartaric acid, N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid and N-methyl-diethanolamine.
[0052] Of course, mixtures of the abovementioned polyols can also be used.
[0053] The polyols should preferably be liquid. The molecular weight should preferably be below 2000 g / mol, in particular below 1500 g / mol (number average molecular weight Mn, determined by GPC). Preference is given to using diols or mixtures thereof.
[0054] Suitable polyamines are aliphatic, cycloaliphatic or arylaliphatic primary diamines, for example ethylenediamine, 1,2-propylenediamine, 1,3-propylenediamine, 2-methyl-1,2-propylenediamine, 2,2-dimethyl-1,3-propylenediamine, 1,3-butylenediamine, 1,4-butylenediamine, 1,3-pentanediamine (DAMP), 1,5-pentanediamine, 1,5-diamino-2-methylpentane (MPMD), 2-butyl-2-ethyl-1,5-pentanediamine (C11-neobutylenediamine), ... diamine), 1,6-hexanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,2,4- and 2,4,4-trimethylhexamethylenediamine (TMD), 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,2-, 1,3- and 1,4-diaminocyclohexane, bis-(4-aminocyclohexyl)methane (H12-MDA) , bis-(4-amino-3-methylcyclohexyl)methane, bis-(4-amino-3-ethylcyclohexyl)methane, bis-(4-amino-3,5-dimethylcyclohexyl)methane, bis-(4-amino-3-ethyl-5-methylcyclohexyl)methane (M-MECA), 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane (isophoronediamine or IPDA), 2- and 4-methyl-1,3-diaminocyclohexane and mixtures thereof , 1,3- and 1,4-bis-(aminomethyl)cyclohexane, 2,5(2,6)-bis-(aminomethyl)bicyclo[2.2.1]heptane (NBDA), 1,4-diamino-2,2,6-trimethylcyclohexane (TMCDA), 1,8-menthanediamine, 3,9-bis-(3-aminopropyl)-2,4,8,10-tetraoxaspiro[5,5]undecane, and 1,3- and 1,4-bis-(aminomethyl)-benzene.
[0055] Other suitable polyamines are aliphatic, cycloaliphatic or arylaliphatic primary triamines, for example 4-aminomethyl-1,8-octanediamine, 1,3,5-tris-(aminomethyl)benzene, 1,3,5-tris-(aminomethyl)cyclohexane, tris-(2-aminoethyl)amine, tris-(2-aminopropyl)amine and tris-(3-aminopropyl)amine.
[0056] Other suitable polyamines are primary aliphatic diamines containing ether groups, such as, in particular, bis-(2-aminoethyl)ether, 3,6-dioxaoctane-1,8-diamine, 4,7-dioxadecane-1,10-diamine, 4,7-dioxadecane-2,9-diamine, 4,9-dioxadodecane-1,12-diamine, 5,8-dioxadodecane-3,10-diamine, 4,7,10-trioxatridecane-1,13-diamine and higher oligomers of these diamines, bis-(3-aminopropyl)polytetrahydrofuran and other polytetrahydrofuran diamines, and polyoxyalkylene diamines. The latter generally represent products of the amination of polyalkylene glycols, such as are available, for example, under the trade name Jeffamine® (from Huntsman), under the name Polyetheramines (from BASF) or under the trade name PC Amine® (from Nitroil). Particularly suitable polyoxyalkylene diamines are Jeffamine® D-230, Jeffamine® D-400, Jeffamine® D-2000, Jeffamine® D-4000, Jeffamine® XTJ-511, Jeffamine® ED-600, Jeffamine® ED-900, Jeffamine® ED-2003, Jeffamine® XTJ-523, Jeffamine® XTJ-536, Jeffamine® XTJ-542, Jeffamine® 250, PC Amine® DA 400, PC Amine® DA 650 and PC Amine® DA 2000.
[0057] Further suitable polyamines are primary polyoxyalkylene triamines which are generally products of the amination of polyoxyalkylene triols and are obtainable, for example, under the name Jeffamine® (from Huntsman), under the name Polyetheramines (from BASF) or under the name PC Amines® (from Nitroil), such as in particular Jeffamine® T-403, Jeffamine® T-3000, Jeffamine® T-5000, Polyetheramine T 403, Polyetheramine T 5000 and PC Amine® TA 403.
[0058] Further suitable polyamines are polyamines having a tertiary amino group and two primary aliphatic amino groups, such as, in particular, N,N'-bis-(aminopropyl)-piperazine, N,N-bis-(3-aminopropyl)methylamine, N,N-bis-(3-aminopropyl)ethylamine, N,N-bis-(3-aminopropyl)propylamine, N,N-bis-(3-aminopropyl)-cyclohexylamine, N,N-bis-(3-aminopropyl)-2-ethyl-hexylamine, and the products from the biscyanoethylation and subsequent reduction of fatty amines derived from natural fatty acids, such as N,N-bis-(3-aminopropyl)dodecylamine and N,N-bis-(3-aminopropyl)tallowalkylamine, obtainable as Triameen® Y12D and Triameen® YT (from Akzo Nos. J. Am.).
[0059] Further suitable polyamines are polyamines containing tertiary amino groups having three primary aliphatic amino groups, such as, in particular, tris-(2-aminoethyl)amine, tris-(2-aminopropyl)amine and tris-(3-aminopropyl)amine.
[0060] Further suitable polyamines are polyamines containing secondary amino groups with two primary aliphatic amino groups, such as, in particular, 3-(2-aminoethyl)amino-propylamine, bis-hexamethylenetriamine (BHMT), diethylenetriamine (DETA), triethylenetetramine (TETA), tetraethylenepentamine (TEPA), pentaethylenehexamine (PEHA) and higher homologs of linear polyethyleneamines, such as polyethylenepolyamines with 5 to 7 ethyleneamine units (so-called “higher ethylenepolyamines”, HEPA), polyamines from the multiple cyanoethylation or cyanobutylation of primary diamines and polyamines with at least two primary amino groups and subsequent hydrogenation. products of hydroxylation, such as dipropylenetriamine (DPTA), N-(2-aminoethyl)-1,3-propylenediamine (N3-amine), N,N'-bis(3-aminopropyl)ethylenediamine (N4-amine), N,N'-bis(3-aminopropyl)-1,4-diaminobutane, N5-(3-aminopropyl)-2-methyl-1,5-pentanediamine, N3-(3-aminopentyl)-1,3-pentanediamine, N5-(3-amino-1-ethylpropyl)-2-methyl-1,5-pentanediamine and N,N'-bis-(3-amino-1-ethylpropyl)-2-methyl-1,5-pentanediamine.
[0061] Further suitable polyamines are polyamines having primary and secondary amino groups, such as, in particular, N-methyl-1,2-ethylenediamine, N-ethyl-1,2-ethylenediamine, N-butyl-1,2-ethylenediamine, N-hexyl-1,2-ethylenediamine, N-(2-ethylhexyl)-1,2-ethylenediamine, N-cyclohexyl-1,2-ethylenediamine, 4-aminomethyl-piperidine, N-(2-aminoethyl)piperazine, N-methyl-1,3-propylenediamine, N-butyl-1,3-propylenediamine, N-(2-ethylhexyl)-1,3-propylenediamine, N-cyclohexyl-1,3-propylenediamine, 3-methyl- The invention also includes the following: 1-amino-1-pentylamine, 3-ethylamino-1-pentylamine, 3-cyclohexylamino-1-pentylamine, fatty diamines such as N-cocoalkyl-1,3-propanediamine, and products from the Michael-type addition reaction of primary aliphatic diamines with acrylonitrile, maleic acid diesters or fumaric acid diesters, citraconic acid diesters, acrylates and methacrylates, acrylic acid amides and methacrylic acid amides and itaconic acid diesters in a 1:1 molar ratio, products from the partial reductive alkylation of primary aliphatic polyamines with benzaldehyde or modified aldehydes or ketones, and partially styrenated polyamines such as Gaskamine® 240 (from Mitsubishi Gas Chemical (MGC)).
[0062] Other suitable polyamines are aromatic polyamines such as, in particular, meta- and para-phenylenediamine, 4,4'-, 2,4'- and 2,2'-diaminodiphenylmethane, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 2,4- and 2,6-toluenediamine, a mixture of 3,5-dimethylthio-2,4- and -2,6-toluenediamine (available as Ethacure® 300 from Albemarle), a mixture of 3,5-diethyl-2,4- and -2,6-toluenediamine (DETDA), 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane (M-DEA), 3,3',5,5'-tetraethyl-2,2'-dichloro-4,4'- M-CDEA, 3,3'-diisopropyl-5,5'-dimethyl-4,4'-diaminodiphenylmethane (M-MIPA), 3,3',5,5'-tetraisopropyl-4,4'-diaminodiphenylmethane (M-DIPA), 4,4'-diaminodiphenyl sulfone (DDS), 4-amino-N-(4-aminophenyl)benzenesulfonamide, 5,5'-methylenedi-o-aminobenzoic acid, (5,5'-methylenedi-o-aminobenzoic acid dimethyl ester), 1,3-propylene bis-(4-aminobenzoate), 1,4-butylene bis-(4-aminobenzoate), polytetramethylene oxide bis-(4-aminobenzoate) (available as Versalink® from Air Products), 1,2-bis-(2-aminophenylthio)ethane, 2-methylpropyl-(4-chloro-3,5-diaminobenzoate), and tert-butyl-(4-chloro-3,5-diaminobenzoate).
[0063] Other suitable polyamines are polyamidoamines which are reaction products of mono- or polyvalent carboxylic acids or their esters or anhydrides, in particular dimerized fatty acids, with a stoichiometric excess of aliphatic, cycloaliphatic or aromatic polyamines, in particular polyalkyleneamines such as DETA or TETA, in particular the commercially available polyamidoamines Versamid® 100, 125, 140 and 150 (from Cognis), Aradur® 223, 250 and 848 (from Huntsman), Euretek® 3607 and 530 (from Huntsman) and Beckopox® EH 651, EH 654, EH 655, EH 661 and EH 664. 663 (from Cytec); and phenolalkylamines, also known as Mannich bases, which are the reaction products of the Mannich reaction of phenols, especially cardanol, with aldehydes, especially formaldehyde, and polyamines, especially the commercially available phenolalkylamines Cardolite® NC-541, NC-557, NC-558, NC-566, Lite 2001 and Lite 2002 (from Cardolite), Aradur® 3440, 3441, 3442 and 3460 (from Huntsman) and Beckopox® EH 614, EH 621, EH 624, EH 628 and EH 629 (from Cytec).
[0064] Preferred polyamines are those selected from the group consisting of 1,3-pentanediamine (DAMP), 1,5-diamino-2-methylpentane (MPMD), 2-butyl-2-ethyl-1,5-pentanediamine (C11-neodiamine), 1,6-hexanediamine, 2,2,4- and 2,4,4-trimethylhexamethylenediamine (TMD), 1,12-dodecanediamine, 1,3-diaminocyclohexane, bis-(4-aminocyclohexyl)methane (H12-MDA), bis-(4-amino-3-methylcyclohexyl)methane, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane (IPDA), 1,3-bis-(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)benzene (MXDA), bis-hexamethylenetriamine (BHMT), diethylenetriamine (D The invention also includes polyoxyethylenediamines and triamines having a molecular weight in the range from 200 to 500 g / mol, in particular Jeffamine® D-230, Jeffamine® D-400 and Jeffamine® T-403 types, polyanilineamines, phenylamines, compounds of the polyamines mentioned which are fully or partially alkylated at the primary amino groups.
[0065] Of course, it is also possible to use mixtures of the abovementioned polyamines.
[0066] Suitable ways to prepare at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines are known per se to those skilled in the art. For example, DE 10315175 or EP 2493951 disclose suitable methods for producing at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines.
[0067] It is important that at least one polyurethane, ie the polymer obtained from the combination of polyisocyanate and polyol and / or polyamine, contains anionic groups. It has been found that such polyurethanes lead to particularly advantageous properties of the rigid inorganic foams of the invention. In particular, polyurethanes having such anionic groups lead to rigid inorganic foams having a low density and increased compressive strength.
[0068] According to an embodiment, the polymer obtained from the combination of the polyisocyanate and the polyol and / or polyamine of the present invention comprises an amount of anionic groups such that the anionic charge density of the polymer is 0.01-100 meq / g polymer, preferably 0.01-10 meq / g polymer, more preferably 0.05-1 meq / g polymer, still more preferably 0.2-0.5 meq / g polymer. Throughout the present invention, the term "meq" stands for "milliequivalent" and refers to the amount of anionic charge (in mmol). The anionic groups are preferably carboxylate groups, sulfonate groups, sulfinate groups, phosphonate groups and / or phosphate groups, especially carboxylate groups.
[0069] Polyurethanes comprising phosphonate groups and / or phosphate groups have the additional advantage of having flame retardant properties.
[0070] The polyurethane with anionic groups of the present invention can be prepared by the reaction of anionic isocyanates with conventional diols, triols, and polyols and / or by the reaction of diols, triols, and polyols with conventional isocyanates. Of course, isocyanates containing anionic groups can be used in combination with isocyanates that do not contain anionic groups. Similarly, diols, triols, and polyols containing anionic groups can be used in combination with diols, triols, and polyols that do not contain anionic groups. Anionic functionalized isocyanates can also be used together with anionic functionalized diols, triols, and polyols, optionally together with isocyanates and / or diols, triols, and polyols that do not carry anionic groups. Particularly suitable diols containing anionic groups are dimethylol propionic acid (DMPA), tartaric acid, N, N-bis (2-hydroxyethyl) -2-aminoethanesulfonic acid and diethyl-bis-(2-hydroxyethyl)-aminomethylphosphonate.
[0071] According to an embodiment, the polyurethane of the invention comprises at least one segment derived from a hydrophobic polyol and at least one segment derived from a difunctional and / or trifunctional polypropylene glycol or polyethylene glycol. Suitable hydrophobic polyols are selected from polypropylene glycol, polytetramethylene glycol (poly(oxytetramethylene) glycol, polyTHF), 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, polyesters obtained by condensation of adipic acid, sebacic acid, glutaric acid, azelaic acid, undecanedioic acid, dodecanedioic acid, 3,3-dimethylglutaric acid, terephthalic acid, isophthalic acid, hexahydrophthalic acid; dimerized fatty acids or mixtures thereof with low molecular weight diols or triols such as ethylene glycol, propylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, dimerized fatty alcohols, glycerol, trimethylolpropane or mixtures thereof. It is particularly preferred that the polyurethane according to the invention comprises at least one chain segment derived from polytetramethylene glycol (poly(oxytetramethylene) glycol, polyTHF). Suitable di- and / or trifunctional polypropylene glycols or polyethylene glycols are in particular linear difunctional polyethylene glycol monomethyl ethers.
[0072] It has been found that particularly stable aqueous dispersions of polyurethanes are produced when the polyurethanes of the invention comprise in their backbone at least one segment derived from a branched monomethyl ether of polypropylene glycol or polyethylene glycol and having two primary hydroxyl groups. This is especially true when the aqueous dispersion of polyurethanes additionally comprises cement, i.e. an aqueous cement paste. Thus, according to an embodiment, at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines comprises at least one segment derived from a branched monomethyl ether of polypropylene glycol or polyethylene glycol having two primary hydroxyl groups.
[0073] The polyurethane of the present invention comprises a backbone obtained by the reaction of a polyisocyanate with a polyol and / or a polyamine. It has been found that the compatibility of the polyurethane of the present invention with at least one surfactant S and / or particle N of the present invention can be increased by optimizing the backbone of the polyurethane. For example, a polyurethane backbone based on a combination of a polyol (especially a hydrophobic polyol) and 4,4'-dicyclohexylmethane diisocyanate is particularly suitable when a protein-based surfactant is to be used. For example, a polyurethane backbone based on a combination of a polyol (especially a hydrophobic polyol) and 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethyl-cyclohexane is particularly suitable when a surfactant based on a sulfonate group is to be used.
[0074] The polymer obtained from the combination of polyisocyanate and polyol and / or polyamine, i.e. the polyurethane, is present in the rigid inorganic foam in an amount of 0.1-20% by weight, preferably 0.5-13% by weight, more preferably 1-8% by weight, still more preferably 2-7% by weight and in particular 5-6% by weight, relative to the total dry weight of the rigid inorganic foam.
[0075] According to an embodiment, the rigid inorganic foam according to the invention may additionally comprise polymers P based on ethylenically unsaturated monomers, in particular vinyl alcohol, vinyl esters, (meth)acrylates, vinyl aromatics, olefins, 1,3-dienes and / or vinyl halides. The additional use of polymers P further increases the mechanical strength, in particular the compressive strength, of the rigid inorganic foam according to the invention.
[0076] Suitable vinyl esters are vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, vinyl laurate, 1-methylvinyl acetate, vinyl pivalate and vinyl esters of α-branched monocarboxylic acids having 9 to 11 carbon atoms, such as VeoVa9R or VeoVa10R (available from Resolution). Suitable (meth)acrylates are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate. Suitable vinyl aromatics are styrene, methylstyrene and vinyltoluene. Suitable vinyl halides are vinyl chloride. Suitable olefins are ethylene and propylene. Suitable 1,3-dienes are 1,3-butadiene and isoprene.
[0077] Particularly suitable polymers P are selected from the group consisting of: (i) copolymers of vinyl acetate with 1 to 50% by weight of ethylene, (ii) copolymers of vinyl acetate with 1 to 45% by weight of ethylene and optionally 1 to 45% by weight of at least one of vinyl propionate, vinyl laurate and vinyl esters of α-branched monocarboxylic acids having 9 to 11 C atoms, (iii) copolymers of vinyl acetate with 1 to 35% by weight of ethylene and 1 to 60% by weight of (meth)acrylic esters of branched or unbranched aliphatic alcohols, in particular n-butyl acrylate or 2-ethylhexyl acrylate, (iv) copolymers of vinyl acetate with 1 to 30% by weight of vinyl laurate, 1 to 35% by weight of ethylene and 1 to 30% by weight of (meth)acrylic esters of branched or unbranched aliphatic alcohols, in particular n-butyl acrylate or 2-ethylhexyl acrylate, (v) copolymers of vinyl acetate with 1 to 40% by weight of ethylene and 1 to 55% by weight of vinyl chloride, (vi) Polyvinyl alcohol having a degree of hydrolysis of 80 to 94 mol % and a Höppler viscosity in a 4% aqueous solution of in particular 1 to 30 mPas (Höppler method according to standard DIN 53015 at 20° C.).
[0078] The polymer P may additionally comprise up to 10% by weight of monomers selected from ethylenically unsaturated carboxylic acids or dicarboxylic acids, ethylenically unsaturated carboxylic acid amides or nitriles, esters of fumaric acid or maleic acid and ethylenically unsaturated sulfonic acids.
[0079] The polymer P may have a glass transition temperature Tg of -25°C to +35°C, preferably -10°C to +15°C, more preferably -10°C to +20°C. Tg can be determined by differential scanning calorimetry known per se. Tg can also be calculated using the Fox equation disclosed in Bull. Am. Phys. Soc. 1, 123 (1956).
[0080] The polymers P are preferably prepared in aqueous medium and preferably by emulsion or suspension polymerization processes as described, for example, in DE-A 102008043988.
[0081] The polymer P additionally comprises a protective colloid. Preferred protective colloids are polyvinyl alcohols, for example partially saponified or fully saponified polyvinyl alcohols, in particular polyvinyl alcohols with a degree of hydrolysis of 80 to 100 mol %. Partially saponified polyvinyl alcohols with a degree of hydrolysis of 80 to 94 mol %, a Höppler viscosity in a 4% aqueous solution, in particular 1 to 30 mPas (Höppler method, 20° C., DIN 53015) are particularly preferred. The protective colloids mentioned can be obtained by methods known to those skilled in the art. The protective colloids are usually present in an amount of 1 to 20% by weight, based on the total weight of the polymer P.
[0082] The polymer P is preferably present in the form of a protective colloid-stabilized powder which is redispersible in water. Dispersing the protective colloid-stabilized, water-redispersible polymer powder gives the protective colloid-stabilized polymer P in the form of an aqueous dispersion. The powder preferably contains 3 to 30% by weight, particularly preferably 5 to 20% by weight, of polyvinyl alcohol, in particular the abovementioned polyvinyl alcohols, based on the dry weight of the powder.
[0083] According to an embodiment, the polymer P is present in the rigid inorganic foam of the invention in an amount of 0.5-30% by weight, preferably 1-25% by weight, more preferably 2-20% by weight and in particular 10-15% by weight relative to the total dry weight of the rigid inorganic foam.
[0084] According to an embodiment, the rigid inorganic foam according to the invention comprises further additives selected from rheology modifiers, thickeners, accelerators, retarders, pigments, biocides, fibers, flame retardants, plasticizers, superplasticizers and / or fillers.
[0085] Thus, according to an embodiment, the rigid inorganic foam according to the invention comprises one or more thickeners selected from polysaccharides (e.g. cellulose ethers and modified cellulose ethers), cellulose esters, starch ethers, guar gum, xanthan gum, polycarboxylic acids (e.g. polyacrylic acid and partial esters thereof), casein and / or associative thickeners.
[0086] According to a further embodiment, the rigid inorganic foam according to the invention comprises an accelerator selected from the group consisting of amino alcohols, alkali metal and alkaline earth metal nitrates, alkali metal and alkaline earth metal nitrites, alkali metal and alkaline earth metal thiocyanates, alkali metal and alkaline earth metal halides, alkali metal and alkaline earth metal carbonates, glycerol, glycerol derivatives, glycols, glycol derivatives, aluminum salts, aluminum hydroxide, alkali metal and alkaline earth metal hydroxides, alkali metal and alkaline earth metal silicates, alkali metal and alkaline earth metal oxides, crystal nuclei, in particular calcium silicate hydrate compounds in finely divided form, and mixtures thereof.
[0087] According to a further embodiment, the rigid inorganic foam according to the invention comprises a retarder selected from phosphates, phosphonates, hydroxycarboxylic acids, in particular citric acid, tartaric acid or lactic acid.
[0088] According to a further embodiment, the rigid inorganic foam according to the invention comprises a plasticizer and / or superplasticizer for an inorganic binder selected from polycarboxylate ethers, polycarboxylates, melamine sulfonates, melamine formaldehyde resins, naphthalene sulfonates and / or lignin sulfonates. However, preferably no or very small amounts of plasticizers or superplasticizers are added.
[0089] According to a further embodiment, the rigid inorganic foam according to the invention comprises sand, in particular river sand or quartz sand, quartz powder, ground limestone, ground dolomite, clay, chalk, slag, rubber particles, aluminum silicate, corundum, basalt, carbides such as silicon carbide or titanium carbide and / or bio-based fillers such as hemp fibers or sunflower pith.
[0090] According to an embodiment, the rigid inorganic foam according to the invention comprises or consists of (relative to the total dry weight of the rigid inorganic foam): a) 9-99% by weight, preferably 25-85% by weight, more preferably 40-80% by weight of at least one solidified mineral binder, preferably at least one cement, especially Portland cement, b) 0.1-25% by weight, preferably 0.5-20% by weight, more preferably 1-15% by weight of at least one surfactant S, c) 0.1-20% by weight, preferably 0.5-13% by weight, more preferably 1-8% by weight, still more preferably 2-7% by weight, in particular 5-6% by weight of at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines, characterized in that the at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines comprises anionic groups, d) optionally 0.5-30% by weight, preferably 1-25% by weight, more preferably 2-20% by weight, still more preferably 10-15% by weight of a polymer P, e) Optionally 0.01-25 wt%, preferably 0.5-20 wt%, more preferably 1-10 wt% of further additives selected from rheology modifiers, thickeners, accelerators, retarders, pigments, biocides, fibers, flame retardants, plasticizers, superplasticizers and / or fillers.
[0091] In a second aspect, the present invention relates to a method for producing a rigid inorganic foam, said method comprising the steps of: (A) providing an inorganic foam, said inorganic foam comprising: a) at least one mineral binder, b) at least one surfactant S and / or particles N, c) at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine, and d) water, characterized in that at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine comprises anionic groups, and (B) curing the inorganic foam of step (A).
[0092] The weight ratio of water to the at least one mineral binder is preferably between 0.2 and 1.5, more preferably between 0.2 and 1.1, still more preferably between 0.4 and 1.1.
[0093] The gas phase contained in the inorganic foam provided in step (A) may be introduced by mechanical, physical or chemical foaming. Non-limiting examples of the gas include air, nitrogen, noble gases, carbon dioxide, hydrocarbons and mixtures thereof.
[0094] For example, the gas phase present in the foam can be introduced by mechanical foaming in the presence of the corresponding gas. Mechanical foaming can be carried out using a kitchen mixer or by an oscillating process or by a stator-rotor process. The gas phase can also be introduced into the foam by physical or chemical foaming, and the physical or chemical foaming process is suitable for releasing gas. Preferably, the foaming agent reacting or decomposing with water and / or acid is used to release gas. The limiting examples of foaming agent include peroxides such as hydrogen peroxide, dibenzoyl peroxide, perbenzoic acid, peracetic acid, alkali metal peroxides, perchloric acid, peroxymonosulfonic acid, dicumyl peroxide or cumyl hydroperoxide, carbonates and bicarbonates such as CaCO , Na CO and NaHCO , it is preferably used in combination with acid, metal powders such as aluminum powder, azide, hydrazide or hydrazine. Foaming by a foaming agent can be helped by using a catalyst.
[0095] In the method of the present invention, it is particularly preferred that at least one polymer obtained by the combination of polyisocyanate and polyol and / or polyamine of the present invention is used in the form of a dispersion in water. Therefore, according to an embodiment, in the method for preparing hard inorganic foam of the present invention, at least one polymer obtained by the combination of polyisocyanate and polyol and / or polyamine is in the form of an aqueous dispersion of the polymer. The solid content of this aqueous dispersion is not particularly limited. The solid content can be 20% to 50% by weight, especially 30% to 40% by weight. The aqueous dispersion of the polymer obtained by the combination of polyisocyanate and polyol and / or polyamine according to the present invention can contain other additives, especially biocides and / or pigments.
[0096] The curing of the inorganic foam usually starts when at least one mineral binder is brought into contact with water. Curing can be carried out, for example, at a temperature between 5-50° C. and a pressure of 1 atm. In this context, curing at higher temperatures and / or higher pressures is not preferred. A hard inorganic foam is obtained when the mechanical strength, in particular the impact resistance, the flexural strength and / or the compressive strength no longer increase significantly over time. Usually, a hard inorganic foam is obtained after hardening for 28 days at 20° C. and 1 atm pressure. Covering the inorganic foam in step (B) is beneficial. Covering prevents rapid evaporation of water and can result in higher compressive strength. The hard inorganic foam can be dried additionally at elevated temperatures, for example at 40-90° C.
[0097] The method for producing the rigid inorganic foam of the present invention can be carried out on a given construction site. Thus, the rigid inorganic foam of the present invention can be carried out on a construction site, for example on a building site or on a construction site where a system using such a rigid inorganic foam is manufactured. The method for producing the rigid inorganic foam of the present invention can also be carried out off-site. Thus, the rigid inorganic foam of the present invention can also be prefabricated and transported to a construction site for installation or transported to a site where the rigid inorganic foam is subsequently used to manufacture other systems.
[0098] The rigid inorganic foam of the present invention can be used in thermal insulation, sound insulation and / or passive fire protection systems. Therefore, in another aspect, the present invention relates to the use of the rigid inorganic foam as described above in a thermal insulation, sound insulation and / or passive fire protection product or system.
[0099] In particular, the rigid inorganic foam of the invention can be used in passive fire protection products or systems complying with standard EAD 350454-00-1104:2017 and / or with category A1 or A2 of standard EN 13501-1.
[0100] According to the embodiment, the rigid inorganic foam of the present invention can be used for thermal insulation, acoustic insulation, lightweight structure and / or passive fire protection. It can be used for horizontal or vertical applications, such as load-bearing structures or non-load-bearing structures, walls, panels, facades, roofs, floors or wall surfaces.
[0101] Alternatively or additionally, the above rigid inorganic foams can also be used to fill cavities. One example is filling cavities in bricks. Another example is filling double walls.
[0102] The following examples will provide the skilled person with additional ways to implement the present invention. Example
[0103] All raw materials are purchased with high quality and used as is.
[0104] Preparation of polyurethane dispersion (PUD)
[0105] The aqueous dispersion of the polymer obtained from the combination of polyisocyanate and polyol and / or polyamine (PUD) of the present invention is prepared as follows:
[0106] In the first step, a prepolymer is prepared from a combination of polyisocyanate and polyol and / or polyamine. The corresponding raw materials for each prepolymer are shown in Table 1 below. Therefore, in a glass reactor equipped with a reflux condenser, a thermometer, a vacuum pump, a dropping funnel and a magnetic stirrer, a linear bifunctional polyethylene glycol monomethyl ether and a corresponding poly (alkylene) glycol are mixed in an amount as shown in Table 1 below. The mixture is heated to 95°C, the pressure is reduced to <50 mbar, and stirring is continued for 10 minutes. Then the corresponding diisocyanate is added at 95°C through a dropping funnel in an amount as shown in Table 1 below and stirring is continued for 10 minutes. Then 0.04% by weight of tin neodecanoate relative to polyalkylene glycol is added and stirring is continued for 30 minutes. Then a mixture of dimethylol propionic acid of a corresponding amount as shown in Table 1 below and 0.04% by weight of tin neodecanoate relative to polyalkylene glycol is added, and stirring is continued for 3 hours. Then the resulting mixture is cooled to obtain a prepolymer obtained by a combination of polyisocyanate and polyol and / or polyamine.
[0107] In the second step, solid NaOH is dissolved in water to achieve a pH of 12.6. The NaOH aqueous solution is heated to a temperature of 85°C with a dissolver under stirring. 38g of the corresponding prepolymer obtained from a combination of polyisocyanate and polyol and / or polyamine (as prepared in the first step above) is added to 54g of an aqueous NaOH solution using a dissolver at 85°C under stirring. Stirring is continued at 1500rpm for 3 minutes. A mixture of 1.9g of ethylenediamine in 6g of water is then added over a 2-5 minute process while stirring at 1000rpm. The temperature of the resulting dispersion is cooled to 23°C and stirring is continued at 1000rpm for 10 minutes. The resulting dispersion is tempered in an oven at 40°C for 16 hours and then placed at 23°C for another 8 hours. Thereafter, the dispersion is filtered through a 100μm filter cloth, and the resulting aqueous dispersion has a solid content of about 40% by weight.
[0108] Table 1: Aqueous dispersions prepared from polymers obtained from combinations of polyisocyanates and polyols and / or polyamines
[0109] Preparation of rigid inorganic foam
[0110] The rigid inorganic foam of the present invention is prepared as follows:
[0111] An apparatus of the "Foamed Concrete Laboratory Mixer - SBL" type from Gertec Maschinen- und Anlagenbau GmbH (Germany) was used. Thereby, an aqueous foam with a predetermined density was prepared in a first container and a cement paste was prepared separately in a second container. Subsequently, the aqueous foam and the cement paste were driven by pressurized air through the static mixing unit of the apparatus to obtain an inorganic foam.
[0112] The cement paste was prepared from 25 kg CEM Type I Portland cement, water in an amount to achieve a water to cement mass ratio of 0.4, 50 g PCE-based superplasticizer, and the type and amount of PUD prepared as described above, as shown in Table 2 below. The water introduced using the PUD was taken into account in calculating the water to cement ratio. Optionally, other polymers as shown in Table 2 below were added to the cement paste. Aqueous foams were prepared from water containing 3 wt % of various surfactants as shown in Table 2 below.
[0113] The production of foam was started with a Gertec SBL machine and was produced by placing a layer with a thickness of 14 cm and a target density as shown in the table below into a mold. The surface of the layer was leveled and the corresponding foam was placed at 23°C / 50% rh. After 1 day, the foam was demoulded and placed at 23°C / 50% rh for a total of 28 days of curing.
[0114] Details of the foam thus produced are reported in Table 1 below.
[0115] After 28 days of curing, the compressive strength was measured according to standard DIN EN 826 at 10% compression.
[0116] The water absorption is measured according to standard DIN EN 16535.
[0117] Table 2 below shows a summary of rigid inorganic foams 1 to 16 and the results.Rigid inorganic foams 1 to 4 are not according to the invention but are provided for comparative purposes.
[0118] Table 2: Rigid inorganic foams produced
[0119] Surfactant A: mixture of C14-C16 alkyl sulfonates, 2-sulfo-succinates Polymer a: copolymer of ethylene and vinyl acetate with high content of vinyl acetate, PVA protective colloid Polymer b: polyvinyl alcohol nm: not measured * amount of polymer calculated in the absence of water
[0120] Table 2: continued
[0121] Table 2: continued
[0122] Surfactant B: Protein-based surfactant
[0123] Table 2: continued
[0124] The expression "brittle" means that the compressive strength cannot be measured because the foam is not strong enough.
Claims
1. A rigid inorganic foam comprising a) at least one cured mineral binder, b) at least one surfactant S and / or particles N, and c) at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine, characterized in that At least one of the polymers obtained from the combination of polyisocyanate and polyol and / or polyamine comprises anionic groups.
2. The rigid inorganic foam according to claim 1, characterized in that The density of the rigid inorganic foam is not more than 500 g / l, in particular not more than 300 g / l, and in particular not more than 200 g / l.
3. Rigid inorganic foam according to at least one of the preceding claims, characterized in that At least one polymer obtained from the combination of polyisocyanate and polyol and / or polyamine of the present invention comprises an amount of anionic groups such that the anionic charge density of the polymer is 0.01-100 meq / g polymer, preferably 0.01-10 meq / g polymer, more preferably 0.05-1 meq / g polymer, still more preferably 0.2-0.5 meq / g polymer.
4. Rigid inorganic foam according to at least one of the preceding claims, characterized in that At least one polymer obtained from the combination of polyisocyanate and polyol and / or polyamine comprises at least one segment derived from the monomethyl ether of branched polypropylene glycol or polyethylene glycol having two primary hydroxyl groups.
5. Rigid inorganic foam according to at least one of the preceding claims, characterized in that At least one polymer obtained from the combination of a polyisocyanate and a polyol and / or a polyamine comprises at least one segment derived from an aliphatic diisocyanate.
6. Rigid inorganic foam according to at least one of the preceding claims, characterized in that It further comprises polymers P based on ethylenically unsaturated monomers, in particular vinyl alcohol, vinyl esters, (meth)acrylates, vinyl aromatics, olefins, 1,3-dienes and / or vinyl halides.
7. The hard inorganic foam according to claim 5, characterized in that The further polymer P is present in an amount of 0.5-30% by weight, preferably 1-25% by weight, more preferably 2-20% by weight, still more preferably 10-15% by weight, relative to the total dry weight of the rigid inorganic foam.
8. Rigid inorganic foam according to at least one of the preceding claims, characterized in that At least one polymer obtained from a combination of polyisocyanate and polyol and / or polyamine is present in an amount of 0.1-20% by weight, preferably 0.5-13% by weight, more preferably 1-8% by weight, still more preferably 2-7% by weight and especially 5-6% by weight relative to the total dry weight of the rigid inorganic foam.
9. Rigid inorganic foam according to at least one of the preceding claims, characterized in that The at least one surfactant S is chosen from nonionic and anionic surfactants, preferably from C14-C16 alkyl sulfonates, esters of 2-sulfosuccinic acid, alkyl polyglucosides or mixtures thereof, or cocoamidopropyl betaine, or protein-based surfactants.
10. Rigid inorganic foam according to at least one of the preceding claims, characterized in that The rigid inorganic foam comprises further additives selected from rheology modifiers, thickeners, accelerators, retarders, pigments, biocides, fibers, flame retardants, plasticizers, superplasticizers and / or fillers.
11. Rigid inorganic foam according to at least one of the preceding claims, comprising or consisting of (in each case relative to the total dry weight of the rigid inorganic foam): a) 9 to 99% by weight, preferably 25 to 85% by weight, more preferably 40 to 80% by weight of at least one solidifying mineral binder, preferably at least one cement, in particular Portland cement, b) 0.1 to 25% by weight, preferably 0.5 to 20% by weight, more preferably 1 to 15% by weight of at least one surfactant S, c) 0.1 to 20% by weight, preferably 0.5 to 13% by weight, more preferably 1 to 8% by weight, still more preferably 2 to 7% by weight, in particular 5 to 6% by weight of at least one polymer obtained from a combination of polyisocyanates and polyols and / or polyamines, d) optionally 0.5 to 30% by weight, preferably 1 to 25% by weight, more preferably 2 to 20% by weight, still more preferably 10 to 15% by weight of a polymer P, e) Optionally 0.01-25 wt. %, preferably 0.5-20 wt. %, more preferably 1-10 wt. % of other additives selected from rheology modifiers, thickeners, accelerators, retarders, pigments, biocides, fibers, flame retardants, plasticizers, superplasticizers and / or fillers, characterized in that At least one of the polymers obtained from the combination of polyisocyanate and polyol and / or polyamine comprises anionic groups.
12. A method for producing a rigid inorganic foam, said method comprising the steps of: (A) providing an inorganic foam comprising: a) at least one mineral binder, b) at least one surfactant S and / or particles N, c) at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine, and d) water, characterised in that at least one polymer obtained from a combination of a polyisocyanate and a polyol and / or a polyamine comprises anionic groups, and (B) curing the inorganic foam of step (A).
13. The method for producing a rigid inorganic foam according to claim 12, characterized in that At least one polymer obtained from the combination of a polyisocyanate and a polyol and / or a polyamine is in the form of an aqueous dispersion of said polymer.
14. Use of the rigid inorganic foam according to at least one of claims 1 to 11 in products or systems for thermal insulation, sound insulation, lightweight construction and / or passive fire protection.
15. Use of the rigid inorganic foam according to at least one of claims 1 to 11 for filling cavities.
Citation Information
Patent Citations
Fiber-containing mortar composition
DE102008043988A1
Electrosterically stabilized aqueous polyurethane resins, processes for their production and their use
DE10315175A1
PU adhesive having viscosity regulator
EP2493951A1
Hybrid foam
WO2019038105A1